Aves ameaçadas do cerrado: Distribuição, associação com a paisagem e perspectivas para conservação - Faggion, Sabrina (2024)
Aim: The study aims to assess the suitability of threatened Cerrado birds in natural forest and open habitats, considering exposure to land use conversion and the capacity of the protected area system to potentially shelter them. Location: Cerrado Biome, Brazil. Methods: We created distribution models for 72 threatened bird species of the Cerrado and calculated regions with higher richness in less exposed forest and open environments to conversion, pointing out the importance of each of these formations for species conservation. Results: Species richness is concentrated in the southern portion of the Cerrado, with all of them being poorly represented in Conservation Units and Indigenous Lands (<23%). Threatened species have different relationships with phytophysiognomies, being both dependent on forest environments and independent. However, they are spatially distributed differently, species independent of forest areas are more typical of the biome and more restricted to open areas, while dependent and semi-dependent occupy the formations similarly. Remaining forest areas occupy a small part of the territory (<6%) compared to open ones (<40%). The amount of areas with high species richness in open formations is at least 70 times greater than in forests, corresponding to the most altered regions in the biome. Main conclusions: Considering the richness of threatened birds of the Cerrado and remaining native areas, protected areas are not sufficient for conservation. Open areas have species more restricted to the formation and characteristics of the Cerrado, making them important for maintaining more exclusive species. 44% of the biome has better preserved remnants, composed of forest environments (5%) and open ones (39%) and should be prioritized for conservation and restoration.